Facile synthesis of hierarchical fern leaf-like Sb and its application as an additive-free anode for fast reversible Na-ion storage. Issue 4 (6th January 2017) - Liang, Liying; Xu, Yang; Li, Yueliang; Dong, Huishuang; Zhou, Min; Zhao, Huaping; Kaiser, Ute; Lei, Yong
Abstract : Hierarchical Sb as an additive-free anode was fabricated to show excellent electrochemical performance for both Na-ion half and full cells. Abstract : Hierarchical Sb was successfully fabricated via a very simple and cost-effective electrochemical deposition method. Morphological and structural characterizations show that the as-prepared Sb has a uniform fern leaf-like structure which is composed of well-crystallized Sb nanoparticles. The formation mechanism of the fern leaf-like Sb was also investigated. The hierarchical Sb exhibits desirable properties for sodium storage, such as high electrical conductivity and large surface area. When used as an additive-free anode for Na-ion batteries, the as-obtained fern leaf-like Sb reveals excellent cycling stability and rate capability. It can afford a high reversible capacity of 589 mA h g −1 over 150 cycles at 0.5 A g −1 and retain a capacity of 498 mA h g −1 at a high rate of 10 A g −1 . Furthermore, a full cell constructed using P2-Na2/3 Ni1/3 Mn2/3 O2 //fern leaf-like Sb also displays remarkably stable and robust Na-storage performance, which includes a high capacity retention of 70% after 100 cycles at 0.5 A g −1 and a large capacity of 370 mA h g −1 at 10 A g −1 . The excellent electrochemical performance of fern leaf-like Sb can be attributed to its morphological and structural features that ensure fast ion and electron transport and a stable electrode structure.